Anonymous and Traceable: A Dynamic Group Signature-Based Cross-Domain Authentication for IIoT - Cunle Deng; Chushan Zhang; Qiaodan Tan (Mathematics)
As the Internet of Things (IoT) continues to evolve, the demand for cross-domain collaboration between devices and data sharing has grown significantly. Operations confined to a single trust domain can no longer satisfy this requirement, so cross-domain access to resources is becoming an inevitable trend in the evolution of the IIoT. Due to identity trust issues between different domains, authorized access is required before resources can be shared. However, most existing cross-domain authentication schemes face significant challenges in terms of dynamic membership management, privacy protection, and traceability. These schemes involve complex and inefficient interactions and fail to meet the dynamic and lightweight requirements of the IIoT. To address these issues, we propose a privacy-preserving and traceable cross-domain authentication scheme based on dynamic group signatures that enables efficient authentication. The scheme supports anonymous authentication via succinct proofs and incorporates a trapdoor mechanism to enable group managers to trace and revoke malicious identities. Additionally, our solution supports efficient joining and revoking of members and implements blacklist-based proof of non-membership. We formally prove the security of the proposed scheme. The experimental results demonstrate that the proposed scheme outperforms others in terms of computational cost and revocation overhead.